Carbazochrome carbon nanotube as drug delivery nanocarrier for anti-bleeding drug: quantum chemical study - Sayiner, Hakan. S.; Kandemirli, Fatma; Dalgic, Serap Senturk; Monajjemi, Majid; Mollaamin, Fatemeh (Springer Science and Business Media LLC, 2021)
Abstract
The interaction between drugs and single-walled carbon nanotubes is proving to be of fundamental interest for drug system of delivery and nano-bio-sensing. In this study, the interaction of pristine CNT with carbazochrome, an anti-hemorrhagic or hemostatic agent was investigated with M06-2X functional and 6-31G* and 6-31G** basis sets. All probable positions of related adsorption for these kind drugs were thought-out to find out which one is energetically suitable. Based on the achieved data, the stronger interactions appeared the oxygen atom of C=O group and nitrogen atom of imine groups. The topology analysis of QTAIM (quantum theory of atoms in a molecule) method was accomplished to understand the properties of interactions between the CNT and Carbazochrome. Frontier molecular orbital energies of all systems, global index including stiffness, softness, chemical Gibbs energies and electrophilicity parameters, as well as some other important physical data such as dipole moment, polarizability, anisotropy polarisibility and hyperpolaribility were calculated, evaluated and then compared together. The essence of the formed bonding model progress along the reaction roots were further validated using electron localization function (ELF) calculations. In addition the total, partial, and overlapping population densities of states were calculated for any further discussion. The highest values of adsorption energies were determined in the range of 18.24) up to (22.12) kcal mol-1 for these kind systems. The acceptable recovery time of 849 s was obtained for the desorption of carbazochrome from the CNT surface under UV-Light. The final results exhibit that carbazochrome can serve as a promising carrier and also as sensitive sensors in any kind of practical application.
Keywords: Models, Molecular; Drug Carriers; CNT; Carbazochrome; Anticancer Drug; Nanotubes, Carbon; Hemostatics; Transporters; Adrenochrome; ELF; Drug Delivery Systems; QTAIM; Polarization; Quantum Theory; Adsorption; Drug Delivery; Derivatives; Algorithms; Density Functional Theory